Новый вид мермитид из жужелицы - Рубцов, И.А. (Вестник зоологии, 1981)
Coccinellimermis (?) andrejevae sp. n. from Carabus sp. is described from the mature postparasitic female found in Dushanbe outskirts (Tajik SSR). The new species differs from other ones of the genus Coccinellimermis in a slender and long body, absence of onchostyle, thickness of cuticle, arrangement of amphids and cercus, structure of chordas ano tropnosomes.